2010
DOI: 10.1371/journal.pone.0015742
|View full text |Cite
|
Sign up to set email alerts
|

The PTEN Phosphatase Controls Intestinal Epithelial Cell Polarity and Barrier Function: Role in Colorectal Cancer Progression

Abstract: BackgroundThe PTEN phosphatase acts on phosphatidylinositol 3,4,5-triphosphates resulting from phosphatidylinositol 3-kinase (PI3K) activation. PTEN expression has been shown to be decreased in colorectal cancer. Little is known however as to the specific cellular role of PTEN in human intestinal epithelial cells. The aim of this study was to investigate the role of PTEN in human colorectal cancer cells.Methodology/Principal FindingsCaco-2/15, HCT116 and CT26 cells were infected with recombinant lentiviruses e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 71 publications
(105 reference statements)
2
44
0
Order By: Relevance
“…6C). The identified positive correlation between transcription of repeats, induction of an IFN response, and sensitivity to 5-aza-dC supports our model in which tumors with reduced p53 function (36)(37)(38) are prone to activation of transcription of repeats under conditions of reduced DNA methylation. These results suggest that the sensitivity of tumor cells with silent repeats to 5-aza-dC (i.e., the drug decitabine approved for treatment of myelodysplastic syndrome and considered for anticancer use) may depend on whether they have functional p53.…”
Section: Structural Properties Of Major Classes Of P53-controlled Repsupporting
confidence: 82%
“…6C). The identified positive correlation between transcription of repeats, induction of an IFN response, and sensitivity to 5-aza-dC supports our model in which tumors with reduced p53 function (36)(37)(38) are prone to activation of transcription of repeats under conditions of reduced DNA methylation. These results suggest that the sensitivity of tumor cells with silent repeats to 5-aza-dC (i.e., the drug decitabine approved for treatment of myelodysplastic syndrome and considered for anticancer use) may depend on whether they have functional p53.…”
Section: Structural Properties Of Major Classes Of P53-controlled Repsupporting
confidence: 82%
“…In subsequent studies, also using human colon cancer cells, it was found that the PtdIns(3,4,5)P 3 3-phosphatase PTEN localizes to the apical membrane explaining the lack of PtdIns(3,4,5)P 3 in that compartment. Indeed, PTEN downregulation disrupted intestinal epithelial polarity and increased the invasiveness of human colon cancer cells (851). A possible link between PtdIns(4,5)P 2 and the apical polarity was established when annexin2, which had been previously shown to bind PtdIns(4,5)P 2 (1268), was found to be enriched in the apical membranes and also to recruit Cdc42, a small GTP binding protein.…”
Section: Epithelial Cell Polaritymentioning
confidence: 99%
“…We next examined the effects of silencing PTEN on centrosome levels of PLK-1 and γ-tubulin during mitosis by immunofluorescence, since both PLK-1 and (phosphatidylinositol-3,4,5-trisphosphate). 13,14 Nuclear PTEN is important for inducing cell cycle arrest and maintaining chromosome stability; these processes are, at least in part, independent of Akt inhibition. 15,16 Interestingly, PTEN −/− mouse embryonic fibroblasts (MEFs) escape taxol-mediated mitotic arrest more quickly than wild type cells, suggesting that PTEN is important for a mitotic spindle checkpoint.…”
Section: Introductionmentioning
confidence: 99%